How accessible and acceptable are current GP referral mechanisms for IAPT for low-income patients? Lay and primary care perspectives. (1st November 2020) - Thomas, F.; Hansford, L.; Ford, J.; Wyatt, K.; McCabe, R.; Byng, R.
Abstract: Background: Improving Access to Psychological Therapies (IAPT) constitutes a key element of England's national mental health strategy. Accessing IAPT usually requires patients to self-refer on the advice of their GP. Little is known about how GPs perceive and communicate IAPT services with patients from low-income communities, nor how the notion of self-referral is understood and responded to by such patients. Aims: This paper examines how IAPT referrals are made by GPs and how these referrals are perceived and acted on by patients from low-income backgrounds Method: Findings are drawn from in-depth interviews with low-income patients experiencing mental distress ( n = 80); interviews with GPs ( n = 10); secondary analysis of video-recorded GP-patient consultations for mental health ( n = 26). Results: GPs generally supported self-referral, perceiving it an important initial step towards patient recovery. Most patients however, perceived self-referral as an obstacle to accessing IAPT, and felt their mental health needs were being undermined. The way that IAPT was discussed and the pathway for referral appears to affect uptake of these services. Conclusions: A number of factors deter low-income patients from self-referring for IAPT. Understanding these issues is necessary in enabling the development of more effective referral and support mechanisms within primary care.